2006
DOI: 10.5432/ijshs.4.265
|View full text |Cite
|
Sign up to set email alerts
|

Can Physical Activity Moderate the Relationship between School Related Stress and Health Complaints among Japanese Elementary School Children

Abstract: This study examined whether subjective health complaints were associated with school-related stress and physical activity among Japanese 6th grade school children and determined the infl uence of physical activity on the relationship between school-related stress and health complaints. In addition, other health practices were examined as moderators of the association between stress and health complaints. A self-administered questionnaire was conducted for 1,978 pupils at 25 public elementary schools throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Therefore, the actual amount of physical activity might have been underestimated. Although the Health Behavior in School-aged Children Study (HBSC) questionnaire, which was used as a reference in the development of the questionnaire for this study, was confirmed to be valid and reliable [19,34,35], it overestimated moderate-to-vigorous physical activity compared with an accelerometer and reported sexual differences in the accuracy of responses [35]. These factors may have influenced the result in the subanalysis.…”
Section: Association Between Physical Activity and Depressive Symptomsmentioning
confidence: 76%
“…Therefore, the actual amount of physical activity might have been underestimated. Although the Health Behavior in School-aged Children Study (HBSC) questionnaire, which was used as a reference in the development of the questionnaire for this study, was confirmed to be valid and reliable [19,34,35], it overestimated moderate-to-vigorous physical activity compared with an accelerometer and reported sexual differences in the accuracy of responses [35]. These factors may have influenced the result in the subanalysis.…”
Section: Association Between Physical Activity and Depressive Symptomsmentioning
confidence: 76%